Neuroprotective Effects of 7, 8-dihydroxyflavone on Midbrain Dopaminergic Neurons in MPP(+)-treated Monkeys - He, Jingjing (Sci Rep, 2016)
Parkinson’s disease (PD) is one common neurodegenerative disease caused by a significant loss of midbrain dopaminergic neurons. Previous reports showed that 7, 8- dihydroxyflavone (7, 8-DHF) as a potent TrkB agonist can mimic BDNF and play neuroprotective roles for mouse dopaminergic neurons. Nonetheless, the safety and neuroprotective effects are unclear in monkey models of PD. Here, we find that 7, 8-DHF could be absorbed and metabolized into 7-hydroxy-8-methoxyflavone through oral administration in monkeys. The half-life time of 7, 8-DHF in monkey plasma is about 4–8 hrs. Furthermore, these monkeys maintain health state throughout the course of seven-month treatments of 7, 8-DHF (30 mg/kg/day). Importantly, 7, 8-DHF treatments can prevent the progressive degeneration of midbrain dopaminergic neurons by attenuating neurotoxic effects of MPP(+) and display strong neuroprotective effects in monkeys. Our study demonstrates that this promising small molecule may be transited into a clinical useful pharmacological agent.